The adventures of leptospires - Shakeeb Arsalaan Bajunid, Siti Farhana Bajunid; Zulkifli, Mohd Amirul Faiz; Azman, Amira Fathini; Mohd Zainul Arifien, Ameerul Adib; Kueh, Harisson; Kumar, Prashanna Raveenda; Amin Nordin, Syafinaz; Saad, Wan Zuhainis (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Many research has been done to study the impact of gamification in education. Most studies have shown tremendous impact in terms of motivation and engagement of students learning by playing games. In view of the rising number of leptospirosis cases and deaths in Malaysia recently, we are creating an awareness program among students through gamification. This is a strategy to educate students on leptospirosis. The gamified experience in this campaign is an alternative to conventional lectures, which can educate this new generation learners more effectively, using technology with their own devices.